Some Operations of Complex Interval-valued Pythagorean Fuzzy Set and its Application - Chinnadurai, V.; Thayalan, S.; Bobin, A. (Communications in Mathematics and Applications, 2021)
In this article, we discuss the notion of the complex interval-valued Pythagorean fuzzy set (CIVPyFS). We present the algebraic operators and aggregation operators of CIVPyFS. A suitable score function for CIVPyFS is developed to rank the alternatives. Finally, two case studies are given. In the first case, we have used CIVPyFWA operator and in the second case CIVPyFWG. Both the results are compared to bring out the effectiveness, reliability and validity of the proposed method.
Keywords: Complex fuzzy set; Complex interval-valued fuzzy set; Complex Pythagorean fuzzy set; Complex interval-valued Pythagorean fuzzy set